2001
DOI: 10.1590/s0100-879x2001000700003
|View full text |Cite
|
Sign up to set email alerts
|

The DNA puff BhB10-1 gene is differentially expressed in various tissues of Bradysia hygida late larvae and constitutively transcribed in transgenic Drosophila

Abstract: We extended the characterization of the DNA puff BhB10-1 gene of Bradysia hygida by showing that, although its mRNA is detected only at the end of the fourth larval instar, BhB10-1 expression is not restricted to the salivary gland, the tissue in which this gene is amplified. Different amounts of BhB10-1 mRNA were detected in other larval tissues such as gut, Malpighian tubules, fat body, brain and cuticle, suggesting that this gene is expressed differentially in the various tissues analyzed. Analysis of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
(33 reference statements)
1
14
1
1
Order By: Relevance
“…Contrary to the results for the Sciara II/9-1 and the Bradysia BhC4-1 genes, the BhB10-1 gene of Bradysia showed constitutive expression in all of the transgenic Drosophila tissues and stages examined (Monesi et al 2001). However, the level of expression was somewhat higher than that observed for the C3-22 gene of Rhynchosciara.…”
Section: Analysis Of the Expression Of The C3-22 Gene In The Transgencontrasting
confidence: 93%
See 2 more Smart Citations
“…Contrary to the results for the Sciara II/9-1 and the Bradysia BhC4-1 genes, the BhB10-1 gene of Bradysia showed constitutive expression in all of the transgenic Drosophila tissues and stages examined (Monesi et al 2001). However, the level of expression was somewhat higher than that observed for the C3-22 gene of Rhynchosciara.…”
Section: Analysis Of the Expression Of The C3-22 Gene In The Transgencontrasting
confidence: 93%
“…The BhB10-1 gene construct contained the entire transcription unit of the gene and included 816 bp of upstream sequence. The absence of stage and tissue specificity could be due to lack of conservation of regulatory elements between Bradysia and Drosophila, but since this transformed fragment only contained 816 bp upstream of the transcription initiation signal, lack of control might also be caused by the absence of specific regulatory elements (Monesi et al 2001). On the other hand, lack of regulatory elements is not expected to be the cause of the constitutive, basal expression observed for the Rhynchosciara C3-22 gene, since 15 kb of upstream region has been included in the transformed fragment.…”
Section: Analysis Of the Expression Of The C3-22 Gene In The Transgenmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva and N. Monesi, unpublished data). Although DNA puff genes have been primarily characterized as genes that are expressed in the salivary gland Lara et al, 1991;Stocker et al, 1996), the expression of DNA puff B10 BhB10-1 gene has been demonstrated in larval tissues other than the salivary gland at the time DNA puff B10 is formed (Monesi et al, 2001). This result indicates that DNA puff genes expression is not necessarily restricted to the salivary gland, the tissue in which DNA puffs are formed.…”
Section: The Bhc4-1 Promoter Region Contains Both a Ring Gland And A mentioning
confidence: 99%
“…Drosophila melanogaster transgenic lineages for the C3-22, BhC4-1, and BhB10 genes are available [53][54][55] and might be useful in such studies.…”
Section: Sequence Analysis Of the C3-22 Amplicon Bent Dna Sitesmentioning
confidence: 99%